The digital transformation requires workplace innovation: an introduction: - Oeij, P.R.A.; Dhondt, S.; Rus, D.; Hootegem, G. van (2019)
This special issue of the International Journal Technology Transfer and Commercialisation contains five contributions. Prior to developing this special issue, a symposium on WPI was held during EURAM18, the yearly international conference of the European Academy of Management, in Reykjavik, Iceland (June 2018), where a number of the articles where presented.